Simulation analysis of the oil/water structure in the downhole with presence of hydrocyclone separator - Jamil, I.E. (Institute of Physics Publishing, 2015)
The maturing oil fields with increasing water production can pose a challenge in terms of produced water handling and disposal issues. This paper presents the modelling and simulation procedure of the two-phase flow of water/oil in a downhole using ANSYS-FLUENT 14 software. The developed procedure successfully simulated the production zone and the interaction of the two fluids in a natural environment where the reservoir pressure is the sole driving force. The results show significant difference of volume distribution in the flows with different oil content. The model can become an essential tool to assist in prediction of the behavior of oil/water mixture flow in the wellbores, and to serve in designing downhole oil/water separators.